Differences in cognitive outcomes between cognitive and non-public school students and private secondary education in Argentina: A multilevel analysis - Cervini, Rubén (Education Policy Analysis Archives, 2003)
In this article, effects of attending public or private schools on cognitive achievement (Mathematics and Language) and on non-cognitive outcomes (attitudes toward Mathematics and educational and success expectations) of students in the last grade of the secondary education in Argentina are explored by means of multilevel analysis. The study examined data of more than 130,000 students of approximately 3,300 high schools, depending on the outcome indicator considered, from the Censo Nacional de Finalización del Nivel Secundario 1998 (High School National Census of 1998). Student's math and language scores were based on standard tests applied to the students at the end of the academic year. Using multilevel linear modeling with three levels (student, school and state), the author found that (i) the relative influence of schools on cognitive achievements is much higher than on non-cognitive outcomes; (ii) there is no difference in Mathematics achievement between public and private schools once socioeconomic and cultural school composition (“peer group”) are controlled for, while private schools have a small advantage over public school in Language achievement; (iii) the most important effect of the public-private dichotomous variable is detected in relation to the distribution of student “success expectations.” The results are discussed in terms of both the “cultural reproduction theory” and the segmentation process of the educational system in Argentina. Some implications for policy are drawn from the analysis.